2017
DOI: 10.26836/ijasrd/2017/v4/i6/4606
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Influencing Factor of Women Employee Morale on Job Satisfaction, Retention and Belongingness

Abstract: There has been a massive influx of women into the workforce in every region of the world. Because of Greater numbers of women are involved in various work force are compel the countries to adopting equal opportunity policies to encourage and enable women to join the labour market. Yet, despite significant progress in education and access to decision-making posts, women's status in the workplace reflects neither their educational achievements nor their work experience. Indeed, women continue to face numerous ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This is confirmed by a significance t of 0.001 (in model 5) or less than 0.05 which indicates that the effect exerted by the take home pay variable is significant on employee performance. The proof of the effect of take home pay on employee performance in this study showed that there are results of study that are in line with various previous studies on similar topics, which stated that take home pay has a significant and positive effect on employee performance in various industries (Wilfred et al, 2014;Seniwoliba, 2015;Calvin, 2017;Ldama & Nasiru, 2020;Umar, 2014).…”
Section: Take Home Pay Towards Employee Performancesupporting
confidence: 90%
See 3 more Smart Citations
“…This is confirmed by a significance t of 0.001 (in model 5) or less than 0.05 which indicates that the effect exerted by the take home pay variable is significant on employee performance. The proof of the effect of take home pay on employee performance in this study showed that there are results of study that are in line with various previous studies on similar topics, which stated that take home pay has a significant and positive effect on employee performance in various industries (Wilfred et al, 2014;Seniwoliba, 2015;Calvin, 2017;Ldama & Nasiru, 2020;Umar, 2014).…”
Section: Take Home Pay Towards Employee Performancesupporting
confidence: 90%
“…When employees are paid well, employees are more likely to feel happy, valued, and considered important by their company. This has implications for increasing job satisfaction and the desire to perform better at work, including providing better service, working collaboratively, and demonstrating more productivity (Seniwoliba, 2015). Third, take home pay is a company mechanism to encourage employees to remain loyal to their jobs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations